Characterization of Titania (TiO2) Catalysts Prepared by Sol-Gel Method - Marwan Marwan; Naoto Azuma; Akinori Maezawa; Shigeo Uchida (Department of Chemical Engineering, Universitas Gadjah Mada, 2003)
Various TiO2 catalysts in powder form were prepared ny sol-gel method and then characterized for X-ray diffraction and BET surface area. VAriation in composistion of reactants, choice of hydrolysing catalyst, calcination temperature, and method of drying were among preparative variable evaluated. Addition Pt, Fe2O3, CuO and SiO2 on the catalysts was also carried out during the initial stage of sol formation. XRD analysis suggest that all catalysts calcined at 450'C were compeltelu in anatase phase. BET surface area of the catalysts revealed that the catalysts prepared using HNO3 as hydrolysing catalyst, have a surface area larger than the commercial Degussa P25 TiO2 catalyst, with the highest area of 126m2/g. The addition of metals resulted in a lower surface area, while silica provided a considerable incdease in surface area, at 257 m2/g. Analyses of isotherms plot and BJH desorption plots suggest that particle pores were dominated by a bottle-like share. However, the photocalatylstic activity of these catalysts in te degradation of sufactant failed to meet the perfomance rating of Degussa P23 TiO2 catalyst, probably due to less access of surfactant into interbal surface of the prepared catalysts. Degradation of the surfactant usidng different particle sizes suggests that the external surface of TiO2 catalysts was important under liquid phase degradation.